Deteksi Sarkasme dan Ironi pada Twitter dengan Mengunakan Metode CNN - Wijaya, Arvanchrist Charlie; Wibawa, I Gede Arta (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p42, 2022)
Sarcasm refers to the use of words with meaning opposite of what is written or said. With this ambiguity, it could be difficult to tell if the message is sarcastic or not. This paper aim to give some method to detect sarcasm in message, especially in a tweets from Twitter. In this paper we will use a convolutional neural network method to classify the tweets. In this paper we got the accuracy of 73,8% training and 74,6% for validation.